KONTESTASI UMAT BERAGAMA (Studi Tentang Perdamaian dan Ketegangan Islam-Kristen di Kota Bekasi) - Ahmad Zamakhsari (Balai Diklat Keagamaan Bandung, 2019)
The contestation phenomenon between Muslim and Christian groups in the context of social-religious relation. This relation affects the conflict and also cohesion (peace). The tensity between Muslim and Christian groups that happened at the arena of preaching and strengthening the reliogion teaching namely mission of bible in Christian (evangelism) and also dakwah islamiyah (amar ma’ruf, nahi’ munkar). The tensity did not rise the conflict and violence because of local wisdoms, namely the dialogue mechanism or rembug kampung that met both groups to reconsile. The peace between Muslim and Christian groups is established because the cooperation, undertanding and the experiences of cultural values gave the room to the both groups to build the solidarity, communication or dialogue and cooperation. Cultural velues such as tepo seliro (emphaty), unggah-ungguh (polite and impolite ethics), lung tinulung (helping each other), giving food each other, visiting each other, rembug (musyawarah/discussion), slametan (thanks giving) are able to be understood and actualized to internalize inclusive attitudes to water the harmony between religions adherents. Therefore concludes that culture is the dominant factor in building the peace relation among the different religions groups (Islam and Christian). If the religions groups had applied the velues of local wisdoms, then the gate of religion harmonious is opened largely. Key words : contestation, Islam, Christian, Peace, conflict